Love Circle Habit Model Based on Quranic Values in Developing Honest and Courageous Character in Early Childhood - Fatimah, Neneng Siti; Nuraisyah, Siti; Fauziah, Rifka; Efendi, Dinda Mulyaman; Tarlam, Alam (Kirana Publisher (KNPub), 2025)
This study analyzes the effectiveness of the Love Circle habituation model based on Qur’anic values in developing honesty and bravery among early childhood students at TK Annahla Sykamandijaya, Subang Regency. Using a descriptive qualitative method, data were collected through observation, interviews, and documentation for four consecutive weeks. Findings indicate a significant improvement: honesty increased from 40% to 78%, and bravery increased from 35% to 82%. Statistical analysis shows growth rates of 95% (honesty) and 134% (bravery). The effect size (Cohen's d) was 2.53 for honesty and 3.13 for bravery, indicating a very strong impact. These improvements align with Qur’anic values such as Surah At-Taubah 119 (honesty) and Al-Baqarah 177 (moral courage). Thus, Love Circle is proven effective as an Islamic Social Emotional Learning (ISEL) model for early childhood character development.